From Urban Involution to Proletarian Transformation - McGee, Terry (Cahiers de géographie du Québec, 1985)
Broad types and stages in the geography of development are identified. Notwithstanding their interest, these approaches have not adequately explained the processes of development, such as growth of wage labour. In earlier studies of these processes, during the sixties and seventies, the author had foreseen that proletarianization of labour would not occur rapidly in Southeast Asia. This proved to be wrong. The basic reason for this lack of foresight was due to the narrow definition of proletarian transformation for which a broader definition is still needed. A model is proposed to better understand how capitalist expansion penetrates non-proletarian activities. Felt needs and patterns of consumption must also be examined. Desire to obtain consumer needs can actually act as a factor of proletarianization. The question of the dislocation of non-proletarian activities appears crucial both in the agricultural and non-agricultural settings and a search for better theoretical understanding of these empirical processes is essential.